Performance of VITEK 2 in the routine identification of bacteria from positive blood cultures in Sulaimani pediatrics’ hospital - Ali , Seenaa M. (Iraqi Journal of Science, 2022)
Sepsis is a major cause of death worldwide among hospitalized patients, however, an accurate and advanced identification method is associated with improved sepsis patient survival. This Retrospective study carried out in Sulaimani pediatric teaching hospital from January 2014 to July 2015 and aimed to compare the effectiveness of VITEK 2 system with traditional manual procedures for identification of pathogenic bacteria in patients with a serious disease like sepsis. The positive blood cultures were divided into two groups; 138 positive cultures identified by conventional manual methods and 104 positive cultures identified by automated VITEK 2 system. The results showed that VITEK 2 system identified 16 genera and 30 species whereas only nine genera with seven species diagnosed by using routine method. The most important result during this study was the identification of five uncommon bacterial genera Kocuria, Leuconostic, Cedecea, Pantoea and Burkhoderia which have never been diagnosed in the microbiology laboratory of the hospital until the modern automated system VITEK 2 use. In conclusion, using VITEK 2 is required to enhance the performance of hospital’s microbiology laboratory which is essential for accurate diagnosis and prompt effective treatment of blood stream infections.